(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, the mechanical properties of composite samples prepared using a conventional and nanomodified matrix were studied. The thickness of the monolayers in the samples was 0,2 μm. It was found in experiments, that the addition of fullerene soot as a nanomodifierled to an increase in the mechanical properties of the samples along the direction of reinforcement. At the same time, an improvement in the quality of the contact of the matrix with the fibers in the samples with the nanomodifier was observed: on the fracture surface, the nanomodified matrix envelops the fibers, while the usual matrix completely exfoliates. The obtained effects of changing the strength of composites can be associated, among other things, with a change in the level of residual stresses arising in composites during nanomodification. Analytical and numerical modeling methods are used to explain these effects.